Feedback : Are they out there?. (18th September 2015) - Wesson, John; Seberkuhn, Seberkuhn
Abstract: In reply to the book review "A lucky, but lonely, planet" (November 2014 p50, http://ow.ly/EWb5J) and the comment "Not so unlikely" by Peter Morgan (Feedback, December 2014 p22), which discussed the likelihood of life existing on other planets.